POTENSI OBJEK WATU KAPAL SEBAGAI DESTINASI GEOWISATA DI DESA SRIMULYO, KECAMATAN PIYUNGAN, KABUPATEN BANTUL - Fandika Agustiyar; Hendry Wirandok; Rois Naimudin (Sekolah Tinggi Pariwisata Sahid Surakarta, 2021)
Sitimulyo village has been known by the public with the tourist destination Watu Kapal. Watu Kapal object has an extraordinary attraction and potential to be developed into geotourism judging by the characteristics of geology, socio-cultural, educational values, conservation and creative economy of the community. This research aims to find out the potential of